LISTA RECENZENTÓW ROCZNIKA 2013 - Studia Psychologica, Redakcja (Studia Psychologica: Theoria et praxis, 2018)
Małgorzata Basińska Mariola Bidzan Dorota Cianciara Jan Cieciuch Krzysztof Fronczyk Barbara Gawda Zbigniew Gaś Zuzanna Górska Konrad Janowski Aleksandra Jaworowska Jarosław Jastrzębski Agnieszka Kałwa Stanisław Kowalik Monika Kowalska-Dąbrowska Bogusława Lachowska Władysław Jacek Paluchowski Konrad Piotrowski Mieczysław Plopa Maria Straś-Romanowska Maciej Stolarski Dariusz Turek Jan Tylka Ludwika Wojciechowska Emilia Wrocławska-Warchala Sabina Zalewska Bogdan Zawadzki